PENGARUH KEDALAMAN YANG BERBEDA TERHADAP HASIL TANGKAPAN UDANG GALAH ( Macrobrachium rosenbergii) DENGAN MENGGUNAKAN ALAT TANGKAP BUBU DI DESA COT SEUMEURENG KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Farah Diana; Teuku Kautsar; Hafinuddin Hafinuddin (JURNAL PERIKANAN TROPIS, 2018)
Shrimp pole vault (Macrobrachium rosenbergii) also known as the Giant Freshwater Shrimp is one type of crustacea, from the family Palamonidae with Macrobrachium rosenbergii species that has the largest size compared to other freshwater shrimp. Shrimp pole vault live in the two habitats,on the larval stadia live in brackish water and return to fresh water in the stadia of juvenile to adult. The purpose of this study to determine the effect of the depth of the catch shrimp by trap fishing gears and the depth effective for catching shrimp in the river by using gear bubu. This research has held from November to December 2015. The method used is statistic covering catches efficient and depth of efficient, as well as tabulatedinto table ANOVA and BNT test displayed in the form of histograms. results showed that, the level of depth of 1 m on station P1 does not get results efficiently for catching shrimp pole vault, depth 2 m on station P2 is equal to the depth of 1 meter does not get results efficiently for catching shrimp pole vault, while the most efficient depth is the depth of 3 m with the 3,520 and the rate of arrests  are efficient at station P3 with catches 9.87%/3.190 grams. Further test results BNT concluded that 5% get the results 194.7181 whereas BNT 1% get the results 322.8951. different depth Levels give an impact on shrimp catches pole vault and the depth level that is effective for catching shrimp pole vault there is at a depth of  3 m.